A Novel Temperature Compensation Method for a MEMS Gyroscope Oriented on a Periphery Circuit. (16th September 2013) - Cao, Huiliang; Li, Hongsheng; Sheng, Xia; Wang, Shourong; Yang, Bo; Huang, Libin
This paper investigates temperature compensation methods used for the scale factor and bias of the MEMS gyroscope within the temperature range from − 40°C to 60°C. The structure and periphery monitor circuit are introduced. Then the determinant elements of the MEMS gyroscope's scale factor are analysed and the results indicate that scale factor is directly proportional to drive amplitude and sense loop gain and is inversely proportional to the frequency gap between two modes. After that, the compensation methods are proposed, the thermal resistor's positive temperature coefficient (tempco) is utilized to calibrate the scale factor's tempco through regulating the drive mode amplitude and the sense loop gain, and each method is applied respectively and the results are contrasted. The test results of the two specimens express that the most effective compensation method could decrease the scale factor's tempco from 693ppm/°C (640ppm/°C) to 250ppm/°C (257ppm/°C), improving it by 63.9% (59.8%). Finally, a method of declining bias's tempco is investigated and implemented after scale factor compensation. A summator with a thermal resistor is utilized at the output level and decreases the bias's tempco from 103.89°/h/°C (100.78°/h/°C) to 9.70°/h/°C (12°/h/°C) improving it by 90.7% (88%). Repeat tests are performed based on two specimens to prove the repeatability and reproducibility of the methods.